(untitled) (Constructionism Conference Proceedings, 2025)
We present parts of a study that focused on the design and implementation of a learning trajectory in a STEM context for promoting spatial reasoning in 8 year-old disadvantaged children. The larger context of the learning trajectory was the earthquake phenomenon. It included tasks in which students built some concrete instruments (e.g., a seismograph) and structures, as well as used some digital tools (e.g., Google Maps, LightBot), in order to explore aspects related to the phenomenon (such as designing escape routes). By having authentic experiences and engaging in hands-on constructions, students were able to perceive or imagine and articulate different spatial sizes, experiment with different measurement strategies and use adequate measuring instruments for each spatial size.